Association of Pulse Wave Velocity With Chronic Kidney Disease Progression and Mortality: Findings From the CRIC Study (Chronic Renal Insufficiency Cohort). Issue 6 (June 2018) - Townsend, Raymond R.; Anderson, Amanda Hyre; Chirinos, Julio A.; Feldman, Harold I.; Grunwald, Juan E.; Nessel, Lisa; Roy, Jason; Weir, Matthew R.; Wright, Jackson T.; Bansal, Nisha; Hsu, Chi-yuan; Appel, Lawrence J.; et al.
Abstract : Patients with chronic kidney diseases (CKDs) are at risk for further loss of kidney function and death, which occur despite reasonable blood pressure treatment. To determine whether arterial stiffness influences CKD progression and death, independent of blood pressure, we conducted a prospective cohort study of CKD patients enrolled in the CRIC study (Chronic Renal Insufficiency Cohort). Using carotid–femoral pulse wave velocity (PWV), we examined the relationship between PWV and end-stage kidney disease (ESRD), ESRD or halving of estimated glomerular filtration rate, or death from any cause. The 2795 participants we enrolled had a mean age of 60 years, 56.4% were men, 47.3% had diabetes mellitus, and the average estimated glomerular filtration rate at entry was 44.4 mL/min per 1.73 m 2 . During follow-up, there were 504 ESRD events, 628 ESRD or halving of estimated glomerular filtration rate events, and 394 deaths. Patients with the highest tertile of PWV (>10.3 m/s) were at higher risk for ESRD (hazard ratio [95% confidence interval], 1.37 [1.05–1.80]), ESRD or 50% decline in estimated glomerular filtration rate (hazard ratio [95% confidence interval], 1.25 [0.98–1.58]), or death (hazard ratio [95% confidence interval], 1.72 [1.24–2.38]). PWV is a significant predictor of CKD progression and death in people with impaired kidney function. Incorporation of PWV measurements may help define better the risks for these important health outcomes in patients with CKDs. Interventions that reduce aortic stiffness deserve study in people with CKD. Abstract : Supplemental Digital Content is available in the text.